MatchTope: A tool to predict the cross reactivity of peptides complexed with Major Histocompatibility Complex I - Mendes, Marcus Fabiano de Almeida; de Souza Bragatte, Marcelo; Vianna, Priscila; de Freitas, Martiela Vaz; Pöhner, Ina; Richter, Stefan; Wade, Rebecca C.; Salzano, Francisco Mauro; Vieira, Gustavo Fioravanti (Frontiers in Immunology, 2022)
The therapeutic targeting of the immune system, for example in vaccinology and cancer treatment, is a challenging task and the subject of active research. Several in silico tools used for predicting immunogenicity are based on the analysis of peptide sequences binding to the Major Histocompatibility Complex (pMHC). However, few of these bioinformatics tools take into account the pMHC three-dimensional structure. Here, we describe a new bioinformatics tool, MatchTope, developed for predicting peptide similarity, which can trigger cross-reactivity events, by computing and analyzing the electrostatic potentials of pMHC complexes. We validated MatchTope by using previously published data from in vitro assays. We thereby demonstrate the strength of MatchTope for similarity prediction between targets derived from several pathogens as well as for indicating possible cross responses between self and tumor peptides. Our results suggest that MatchTope can enhance and speed up future studies in the fields of vaccinology and cancer immunotherapy.